Improved vaccine platform for safe and effective control of Bovine Viral Diarrhea Virus - Sangewar, Neha (Kansas State University, 2021)
Bovine Viral Diarrhea Virus (BVDV), a Pestivirus with single stranded viral genome, is prevalent in cattle. Commercial BVDV vaccines have many side effects and are not completely protective because BVDV strains are highly diverse. Biosecurity control measures coupled with BVDV vaccination are practiced to minimize incidences of BVDV infection within herds, but BVDV still persists in cattle herds in many places in the world. Hence, the objective of the first study was to address the lack of a safe and efficacious BVDV vaccine. A prototype subunit vaccine comprising of mosaic BVDV antigens, envelop (E2) and non-structural (NS2-3) antigens, from BVDV type 1a, 1b, and 2 along with unique as well as shared B cell and CD4+ T cell epitopes was generated. The mosaic BVDV antigens were shown to be highly immunogenic in calves and elicited broadly neutralizing antibody responses against diverse BVDV-1a, -1b, and -2a strains. The mosaic antigens also induced strong BVDV-1 and -2 cross-reactive bovine CD4⁺ T cell responses. Following BVDV-1b challenge, the prototype vaccine conferred better protection than a commercial killed virus (KV) vaccine as judged by significant (p < 0.05) reduction in viremia and BVD disease in the vaccinated calves. The results from this study therefore indicated that a rationally designed multi-epitope BVDV subunit vaccine can offer broader protection than a commercial BVDV vaccine containing inactivated BVDV-1a, -1b, and -2a strains. In the second study, twenty-eight novel CD8⁺ T cell epitopes were identified from various BVDV antigens. The identified IFN-[gamma]-inducing CD8⁺ T cell epitopes were conserved across >200 BVDV-1 and -2 strains. These highly conserved CD8⁺ T cell epitopes can prime broadly reactive CD8⁺ T cells against multiple BVDV strains in cattle. Future analyses of the novel well-conserved BVDV epitopes for the induction of cytotoxic CD8⁺ T lymphocyte (CTL) responses will lead to the identification of protective determinants that can be included in a subunit BVDV vaccine. Altogether, the knowledge generated by the studies outlined in this thesis will form a basis for development of more efficacious contemporary BVDV vaccines capable of conferring broad protection against diverse BVDV strains.
Keywords: Bovine Viral Diarrhea Virus; Subunit vaccine; Cross-protection; Highly conserved epitopes; Cattle; CD8+ T cell epitopes